INFLUENCE OF CUTTING ZONE COOLING METHOD ON CHIP FORMING CONDITIONS - E. E. Feldshtein; R. Maruda; M. A. Kornievich (Наука и техника)
The paper considers an influence of a cutting zone cooling method on the chip shape and thickening ratio while turning R35 steel with the hardness of НВ 1250 МРа. Cutting with various types of cooling - dry, compressed air and emulsion fog has been investigated in the paper. OPORTET RG-2 emulsol with emulsion concentration of 4% has been used as an active substation. Cutting tool is a turning cutter with a changeable square plate SNUN120408 made of Р25 hard alloy with multilayer wear-resistant coating, upper titanium nitride layer. Front plate surface is flat. Range of cutting speeds - 80-450 m/min, motions - 0,1-0,5 mm/rev, emulsion flow - 1,5-3,5 g/min and compressed air - 4,5-7,0 m3/h, cutting depth - 1,0 mm. In order to reduce a number of single investigations it is possible to use plans based on ЛПх-sequences.It has been shown that the method for cutting zone cooling exerts significant influence on conditions for chip formation. Regression equation describing influence of machining conditions on Ка-chip thickening ratio has been obtained in the paper. The range of cutting modes is extended while using emulsion fog for cooling. In the process of these modes chip is formed in the shape of short spiral fragments or elements. Favourable form of chips is ensured while using the following rate of emulsion - not more than 2 g/min. The investigations have made it possible to determine conditions required for cooling emulsion fog. In this case it has been observed minimum values in chip thickening ratio and chip shape that ensures its easy removal from cutting zone. While making dry turning values of Ка is higher not less than 15 % in comparison with other methods for cutting zone cooling.